Challenges in environmental law enforcement: Exploitation of natural resources under the guise of sustainable development - Fazri, Muhammad Ashabil (Maliki Interdisciplinary Journal, 2026)
Environmental law enforcement in Indonesia faces significant challenges as natural resource exploitation is often disguised as the slogan of sustainable development. In practice, claims of sustainable development often serve as a shield for activities that damage ecosystems and exacerbate environmental degradation. This situation creates a paradox between the good intentions of environmental protection and the reality on the ground, which is far from ideal. This article critiques how the concept of sustainable development is often misused by actors with economic and political interests, resulting in environmental laws, which are supposed to maintain ecological balance, becoming weak and ineffective. Using a critical approach, this article explains the main obstacles to law enforcement, ranging from overlapping regulations and weak oversight to environmental criminalization with minimal deterrent effect. It also discusses the roles of government, private sector, and civil society actors, who often have conflicting interests in natural resource management. By examining this issue from the perspective of a student concerned with and critical of the future of the environment, this article invites readers to understand the issue not only normatively but also the socio-political realities behind sustainable development. Finally, the proposed solution emphasizes the importance of synergy between firm law enforcement, transparency, and active community participation as the key to safeguarding natural resources for true sustainability.